Studi Etnobotani Pulau Enggano, Provinsi Bengkulu - Dhanang Puspita; Sigit E. Prasetyo (Jurusan Biologi FMIPA Universitas Cenderawasih, 2023)
Enggano is one of the leading islands in Indonesia that has unique biodiversity. This uniqueness arises because Enggano is an ocean island that stands alone without ever becoming one with the mainland of Sumatra. Regarding its biodiversity, ethnobotany studies are needed to find out the culture of the Enggano people from ancient times to the present in the use of plants to support their lives. The Enggano people are familiar with plants that are used as food, construction, medicine, and simple technology and are still used today. The local knowledge of the Enggano community about the use of plants can provide support for their existence. Key words: culture; Enggano; ethnobotany; plant.